Air pollution associated with non-suicidal self-injury in Chinese adolescent students: A cross-sectional study. (October 2018) - Liu, Weina; Sun, Hong; Zhang, Xin; Chen, Qi; Xu, Yan; Chen, Xi; Ding, Zhen
Abstract: Background: Non-suicidal self-injury (NSSI) is a frequent phenomenon in adolescents and is closely related to eventual suicide. Although the effect of air pollution on various diseases has been extensively investigated, no studies examined its effect on NSSI in young students. Objectives: We investigated the effect of air pollution on NSSI in Chinese students. Methods: We investigated the incidence of NSSI in the past 12 months in 54 923 Chinese students with an anonymous questionnaire. We assessed the air pollution exposure of each student by the air quality matched with their schools, which were calculated by the inverse distance weighting method from the environmental monitoring data. We discussed the association between ambient air pollutants and the incidence of NSSI using generalized additive mixed models. Results: A 10 μg/m 3 increase in the annual moving average concentration of particulate matter with diameters less than 2.5 μm (PM2.5 ) and ozone (O3 ) was associated with a 13.9 percent and a 10.5 percent increase in the odds ratio (OR) of NSSI, respectively. In addition, a 0.1 mg/m 3 increase in the annual moving average concentration of carbon monoxide (CO) was associated with a 4.8 percent increase in the OR of NSSI. NO2 and SO2 were not related to NSSI. CO and O3 show non-linear effects on NSSI. Male students in high school are the most s to the effects of PM2.5 on NSSI. Conclusions: Our study suggests that increases in PM2.5, O3 and CO may increase the incidence of NSSI among adolescent students. Highlights: PM2.5, ozone, and CO are positively associated with non-suicidal self-injury (NSSI) in Chinese adolescent students. O3 and CO showed a non-linear association with NSSI. Male students in high school were the most susceptible to the effects of PM2.5 on NSSI.